From Citizenship Transmission to Transformative Pedagogy: The Evolving Traditions of Social Studies Education - Asep, Asep; Sapriya, Sapriya; Salira, Ade Budhi; Devi, Meila Yufriana (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2026)
This systematic literature review analyzes the global evolution of Social Studies Education traditions through thematic analysis of 59 Scopus-indexed articles published between 2016 and 2026. Framed by four traditions Citizenship Transmission, Social Science, Reflective Inquiry, and Social Transformation. The study examines how globalization, mass migration, and political polarization reshape the field. It maps shifts in traditions, identifies pedagogical innovations, diagnoses barriers to transformative practice, and proposes a cohesive scientific framework. Findings show a movement from transmission-centered models toward integrative and critical pedagogies, although a gap persists between transformative rhetoric and classroom practice. Key themes include critical citizenship, curriculum decolonization, the affective turn, civic reasoning, and teacher education reform. The review recommends integrative approaches, including the C3 Framework, with a stronger emphasis on affective dimensions and decolonization to prepare empowered global citizens. Its novelty lies in its cross-national synthesis and unified foundation for social studies as a transformative discipline.